Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/0363546518796830
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Persistent Postconcussion Symptom Risk in a Pediatric Sports Medicine Clinic

Abstract: Background: Although most children report symptom resolution within a month of a concussion, some patients experience persistent postconcussion symptoms (PPCS) that continues for more than 1 month. Identifying patients at risk for PPCS soon after an injury can provide useful clinical information. Purpose: To determine if the Predicting Persistent Post-concussive Problems in Pediatrics (5P) clinical risk score, an emergency department (ED)–derived and validated tool, is associated with developing PPCS when obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 33 publications
1
56
1
Order By: Relevance
“…75,[81][82][83] History of prior mTBI(s) 75,76,84,85 and typical intracranial abnormalities on day-ofinjury CT (eg, subdural hematoma) 76,86 have been inconsistent predictors of clinical outcome. The more symptoms a patient has soon after mTBI, the more symptoms they tend to have weeks and months later 81,[83][84][85] In adults, preinjury mental health problems and postinjury psychological distress (symptoms of depression and anxiety) are robust predictors of prolonged recovery. 76,81,83,85,87 Treatment Early clinical management.…”
Section: Prognosismentioning
confidence: 99%
“…75,[81][82][83] History of prior mTBI(s) 75,76,84,85 and typical intracranial abnormalities on day-ofinjury CT (eg, subdural hematoma) 76,86 have been inconsistent predictors of clinical outcome. The more symptoms a patient has soon after mTBI, the more symptoms they tend to have weeks and months later 81,[83][84][85] In adults, preinjury mental health problems and postinjury psychological distress (symptoms of depression and anxiety) are robust predictors of prolonged recovery. 76,81,83,85,87 Treatment Early clinical management.…”
Section: Prognosismentioning
confidence: 99%
“…According to one group, there are 9 “clinical risks” associated with persistent post‐concussive symptoms in pediatrics: being a teenage female, having a prior prolonged recovery from a previous mTBI, a higher somatic symptom score post‐injury (including headache, sensitive to noise, fatigue, and cognitive slowing) and/or >4 errors on the balance error scoring system (BESS) 14,120 . A further study suggested that it is likely a constellation of factors, including a history of mood disorders, prior mTBI, and delayed symptom onset (possibly a marker of maladaptive coping), that leads to an increased risk for both PPTH and persistent PCS 24 .…”
Section: Return To Learn and Return To Play (Rtl/rtp) Post‐mtbimentioning
confidence: 99%
“…28 Recent work has indicated that postural instability, defined as more than three errors during the tandem stance of the BESS test, is associated with prolonged symptom duration in patients seen in both the ED and sports medicine clinic settings. 20,44 In addition to postural instability assessment, the Romberg test may also serve as a method to determine if patients are exaggerating their postinjury deficits in a manner that reflects balance dysfunction. 42 The idea that some youths may exaggerate or feign symptoms after concussion has been studied in the context of neuropsychological testing and symptom reporting, 1,7,26 but it has not received substantial attention with regard to postural stability tests.…”
Section: Discussionmentioning
confidence: 99%
“…44 In addition, recently investigators applied this approach to the sports medicine setting and were able to successfully identify those patients at risk for persistent symptoms. 20 A particularly vulnerable time in life for developing persistent symptoms after a concussion is the teenage years, during which girls may carry a higher risk than boys. 22 Several other noninjury factors that have been associated with concussion recovery time include previous concussions, attention-deficit/hyperactivity disorder (ADHD), learning disability, prior psychiatric history, and migraine history.…”
mentioning
confidence: 99%